The Effect of a High-Fat Breakfast on the Pharmacokinetics of Moxidectin in Healthy Male Subjects: A Randomized Phase I Trial - Korth-Bradley, Joan M.; Parks, Virginia; Chalon, Stephan; Gourley, Ian; Matschke, Kyle; Cailleux, Karine; Fitoussi, Serge; Fleckenstein, Lawrence (The American journal of tropical medicine and hygiene, 2012)
The objective of this study was to assess the effect of a high-fat meal on the pharmacokinetics of moxidectin. Healthy male subjects were randomized to receive single oral 8 mg doses of moxidectin after an overnight fast or high-fat breakfast. In fasted subjects ( N = 27), mean [SD] parameters were C max : 58.9 [12.5] ng/mL; t max : 3.7 [1.5] h; area under concentration-time curve (AUC): 3,387 [1,328] ng/h/mL; Vλ z /F: 2,829 [1,267] L; CL/F: 2.76 [1.28] L/h; and t ½ : 784 [347] h. Compared with fasted subjects, fed subjects ( N = 27) exhibited a 34% increase in C max , delay in t max to 5.3 [2.1] h, 44% increase in AUC, 40% decrease in Vλ z /F, and a 35% decrease in CL/F. There was no significant change in t ½ . The changes are consistent with an increase in moxidectin bioavailability following administration with food. There were no clinically relevant changes in vital signs, laboratory tests, or electrocardiograms.